(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Since last few years technical advancements have opened new doors for marketers. Extended Reality(XR), a board term representing Mixed Reality(MR), Virtual Reality(VR) and Augmented Reality(AR) (Milgram & Kishino, 1994); is an emerging integration of IT and Marketing that delivers meaningful results to marketing strategies by delivering immersive product experience to audiences. In continuation of past researches on Extended Reality, this study is exclusively focused on awareness, likability, acceptability and feasibility of Extended Reality for marketing communication tool, keeping audience’s perspectives at center. Research findings are primarily based on data collected through structured questionnaire and supported through literature review. 150 numbers of respondents were asked with series of questions strategically designed to achieve research objectives. Research study is concluded with further scope of study in subject discipline.